Enhancing English Vocabulary Acquisition in Early Childhood Learners Through a Structured Flashcard Program - Sicilia Triana Medianti Prantyastuti; Hendrawan Armanto (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2026)
This Classroom Action Research was conducted to improve English vocabulary mastery and learning engagement among early childhood students. The intervention involved the use of illustrated flashcards combined with collaborative group games. The study participants consisted of 23 students from a Kindergarten B class. Data were collected using quantitative tests, qualitative observation sheets, and field notes. The research was carried out in three stages: the pre-cycle, Cycle 1, and Cycle 2. The results demonstrated significant improvement in both learning outcomes and student behavior during instruction. Quantitatively, the class mastery rate rose from 13.04% in the pre-cycle stage to 52.17% in Cycle 1, eventually reaching 86.96% by the end of Cycle 2. These results surpassed the established success target of 75%. Qualitatively, the use of tangible visual aids and enjoyable group activities helped alleviate the children's anxiety when learning English. Students who were previously inclined to be passive and easily distracted became more active, gained confidence in pronouncing vocabulary, and engaged more effectively with the lessons. Thus, the use of visual flashcards combined with group games proved effective in enhancing the children's English language skills while also fostering their social-behavioral development in the classroom.